Effects of Ketamine on Levels of Inflammatory Cytokines IL-6, IL-1β, and TNF-α in the Hippocampus of Mice Following Acute or Chronic Administration - Li, Yanning; Shen, Ruipeng; Wen, Gehua; Ding, Runtao; Du, Ao; Zhou, Jichuan; Dong, Zhibin; Ren, Xinghua; Yao, Hui; Zhao, Rui; Zhang, Guohua; Lu, Yan; et al. (Frontiers in Pharmacology, 2017)
Ketamine is an injectable anesthetic and recreational drug of abuse commonly used worldwide. Many experimental studies have shown that ketamine can impair cognitive function and induce psychotic states. Neuroinflammation has been suggested to play an important role in neurodegeneration. Meanwhile, ketamine has been shown to modulate the levels of inflammatory cytokines. We hypothesized that the effects of ketamine on the central nervous system are associated with inflammatory cytokines. Therefore, we set out to establish acute and chronic ketamine administration models in C57BL/6 mice, to evaluate spatial recognition memory and emotional response, to analyze the changes in the levels of the inflammatory cytokines interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) in the mouse hippocampus, employing behavioral tests, Western blot, quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) and immunohistochemistry. Our results showed that ketamine at the dose of 60 mg/kg induced spatial recognition memory deficit and reduced anxiety-like behaviors in mice after chronic administration. Moreover, we found that ketamine increased the hippocampal levels of IL-6 and IL-1β after single, multiple and long-term administration in a dose-dependent manner. However, the expression level of TNF-α differed in the mouse hippocampus under different conditions. Single administration of ketamine increased the level of TNF-α, whereas multiple and long-term administration decreased it significantly. We considered that TNF-α expression could be controlled by a bi-directional regulatory pathway, which was associated with the dose and duration of ketamine administration. Our results suggest that the alterations in the levels of inflammatory cytokines IL-6, IL-1β and TNF-α may be involved in the neurotoxicity of ketamine.